A prática de liberdade na perspectiva freiriana : a experiência socioeducativa no CASENH - Hennemann, Mariana Vanini (Universidade do Vale do Rio dos Sinos, 2017)
In this research the subjects are male adolescents, they are between fifteen and nineteen years old, and are considered "in conflict with the law", since they practiced acts that violated the laws of coexistence established in that country. The aim was to understand the perspectives of educating adolescents to practice freedom in a deprivation system. The methodology is inspired by participatory research and systematization of experiences, through which we perceive the interweaving between the thematic work - in Freirean perspective and the adolescents’ speeches selected from the recordings - with the values of the restorative justice. Some adolescents’ narratives became indispensable to the text because of thecontext of theexperiencelived by each one in the deprivation of freedom. The experiences in the context of deprivation of liberty lived by Frei Betto and especially Paulo Freire inspired the writing of this dissertation. Based on the research, we turned to the theorizing of socio-educational practices aimed towards adolescents in situations of deprivation of liberty. This is based on the construction of what is socio-education in a dialogue with the main issues raised during the research: liberating education, Socio-education and Restorative Justice. There are also some (dis)encounters between the Restorative Justice and the education, considering their contributions to the practice of freedom in Freirian perspective with adolescents, based on four restorative values: accountability, dialogue (interconnection), participation and hope. Through this experience it was possible to perceive that the institutional space can be a possible space for reflections and production of liberating paths, but the opportunities for listening and dialogue between adolescents and for them to do that with professionals is still limited to the infraction process of each one, strengthening the punitive rather than the educational character. In this context, in our understanding, implementing socio-education as a new pedagogy, with its specificities, in the field of socio-educational measures of deprivation of liberty, is still a practice in construction, necessary to be (re)thought, in the face of the social question in contemporary time, as well as in the midst of the institutional reality that still presents itself as a payment of debt or punishment for adolescents.
Keywords: Adolescentes; Privação de liberdade; Paulo Freire; Socioeducação; Justiça restaurativa; Adolescents; Deprivation; Freedom; Paulo Freire; Socioeducation; Restorative justice; ACCNPQ::Ciências Humanas::Educação